The species of the genus Crataegus L. in the National Nature Park ‘Podilskyi Tovtry’ (Podolian Hills, Western Ukraine) - Sołtys-Lelek, Anna; Oliіar Halyna (Biodiversity: Research and Conservation, 2016)
The paper presents an inventory of hawthorns occurring in the National Nature Park ‘Podilskyi Tovtry’. 8 taxa were recorded based on the field studies during the years 2009-2013, as well as on the published data. Four of them are new for the flora of the Park’s area: C. × macrocarpa Hegetschw., C. × subsphaericea Gand., C. × media Bechst., and the triple hybrid C. monogyna Jacq. × C. laevigata (Pior.) DC. × C. rhipidophylla Gand.